Impact of pre-transplant body mass index on outcomes in AML patients aged ≥ 50 years after allogeneic hematopoietic cell transplantation - Guo, Wenwen; Zhang, Haixiao; Gao, Hongye; Zheng, Yawei; Wang, Mingyang; Cao, Wenbin; Zhang, Rongli; Ma, Qiaoling; He, Yi; Zhai, Weihua; Yang, Donglin; Pang, Aiming; et al. (Frontiers in Immunology, 2025)
IntroductionThe prognostic significance of body mass index (BMI) in elderly acute myeloid leukemia (AML) patients undergoing allogeneic hematopoietic cell transplantation (allo-HCT) remains controversial.MethodsThis retrospective study analyzed 142 AML patients aged ≥50 years receiving allo-HCT (2013-2022), stratified by Chinese BMI criteria: low BMI (<24 kg/m², n = 83) vs. high BMI (≥24 kg/m², n = 59).ResultsThe median pre-transplant BMI was 23.63 (IQR, 22.07-25.78) kg/m². Multivariate analysis identified BMI <24 kg/m² as an independent risk factor for inferior OS (HR=1.80, p=0.037) and GRFS (HR=2.00, p = 0.003). Although BMI did not correlate with relapse, long-term non-relapse mortality (NRM), or the incidence of acute and chronic graft versus host disease (GVHD), the one-year NRM was significantly higher in the low BMI group compared to the high BMI group (p = 0.006). Subgroup analysis revealed that high-risk patients [not complete remission (NR) or CR but minimal residual disease (MRD)-positive) with low BMI had markedly reduced 3-year OS (20.87% vs. 57.69%, p=0.006), whereas no difference was observed in low-risk (CR/MRD-negative) patients.DiscussionPre-transplant BMI independently predicts inferior survival in older adults with AML undergoing allo-HCT. These findings highlight the need for BMI-guided nutritional interventions, especially for high-risk older patients.